On dispersion above a forest—Measurements and methods. (2nd August 2016) - Hicks, B.B.; Hunter, C.H.; Weber, A.H.
ABSTRACT: Data collected over a mixed conifer/deciduous forest at the U.S. Department of Energy's Savannah River Site in South Carolina using sonic anemometry reveal that on-site and real-time measurements of the velocity component standard deviations, σ v and σ w, are preferred for dispersion modeling. Such data are now easily accessible, from the outputs of cost-effective and rugged sonic anemometers. The data streams from these devices allow improvements to conventional methodologies for dispersion modeling. In particular, extrapolation of basic input data from a nearby location to the site of the actual release can be facilitated. In this regard reliance on the velocity statistics σv and σw appears to be preferred to the conventional σθ and σϕ . In the forest situations addressed here, the uncertainties introduced by extrapolating initializing properties ( u, θ, σθ, and σϕ, or alternatively, σ v and σ w ) from some location of actual measurement to some nearby location where an actual release occurs are similar to those associated with the spread of the plume itself and must be considered in any prediction of the likelihood of downwind concentration (exposure) exceeding some critical value, i.e., a regulatory standard. Consideration of plume expansion factors related to meander will not necessarily cause predicted downwind maxima within a particular plume to be decreased; however, the probability of exposure to this maximum value at any particular location will be reduced. Three-component sonic anemometers are affordable and reliable, and are now becoming a standard for meteorological monitoring programs subject to regulatory oversight. The time has come for regulatory agencies and the applied dispersion community to replace the traditional discrete sets of dispersion coefficients based on Pasquill stability by the direct input of measured turbulence data. Implications : The continued endorsement of legacy Pasquill-Gifford stability schemes is presently under discussion among professional groups and regulatory agencies. The present paper is an attempt to introduce some rationality, for the case of a forested environment.